Knowledge and acceptability of epidural analgesia for labor on Maternal Perinatal National Institute- 2011 - admin, admin (2018)
Objectives. Determine the level of awareness and acceptability of pregnant women to epidural labor analgesia anesthesiologist intervention in the Maternal Perinatal Specialized Institute. Materials and methods. This is a Observational, prospective, longitudinal study in the service of psycho-prophylaxis of the Maternal Perinatal Specialized Institute, conducted at 205 pregnant women. Results. The level of knowledge of pregnant women on epidural labor analgesia through of anesthesiologist intervention in the Maternal Perinatal Specialized Institute is 55,9%, its level of acceptance is 42,9%, the grounds (factors) that decrease the acceptance of labor analgesia are: Fear of being damaged your health (67,8%) and fear of harming your baby (32,2%). Finally, the percentage of pregnant women satisfied with the information you received is 69,3%, but only admit you would like to receive epidural analgesia in labor an 42,4% , while 26,8% do not want to receive or has doubts for receive this procedure. Conclusion. The level of knowledge of pregnant women is 55,9% and 42,9% acceptability of epidural labor analgesia for anesthesiologist intervention in Maternal Perinatal National Institute.